Fluorine impairs carboxylesterase 1-mediated hydrolysis of T-2 toxin and increases its chondrocyte toxicity - Jia, Yumeng; Shi, Sirong; Cheng, Bolun; Cheng, Shiqiang; Liu, Li; Meng, Peilin; Yang, Xuena; Chu, Xiaoge; Wen, Yan; Zhang, Feng; Guo, Xiong (Frontiers in Nutrition, 2022)
Background: T-2 toxin is recognized as one of the high-risk environmental factors for etiology and pathogenesis of Kashin-Beck disease (KBD). Previous evidence indicates decreased serum fluorine level in KBD patients. However, whether fluoride could regulate carboxylesterase 1 (CES1) mediated T-2 toxin hydrolysis and alter its chondrocyte toxicity remains largely unknown. Methods: In this study, in vitro hydrolytic kinetics were explored by using recombinant human CES1. HPLC-MS/MS was used to quantitative determination of hydrolytic metabolites of T-2 toxin. HepG2 cells were treated with different concentration of sodium fluoride (NaF). qRT-PCR and western blot analysis were used to compare the mRNA and protein expression levels of CES1. C28/I2 cells were treated with T-2 toxin, HT-2 toxin and neosolaniol (NEO), and then cell viability was determined by MTT assay, cell apoptosis was determined by Annexin V-FITC/PI, Hoechst 33258 staining and cleaved caspase-3, and cell cycle was monitored by flow cytometry assay, CKD4 and CDK6. Results: We identified that recombinant human CES1 was involved in T-2 toxin hydrolysis to generate HT-2 toxin, but not NEO, and NaF repressed the formation of HT-2 toxin. Both mRNA and protein expression of CES1 were significantly down-regulated in a dose dependent manner after NaF treatment in HepG2 cells. Moreover, we evaluated the chondrocyte toxicity of T-2 toxin and its hydrolytic metabolites. Results showed that T-2 toxin induced strongest cell apoptosis, followed by HT-2 toxin and NEO. The decreased the proportion of cells in G0/G1 phase was observed with the descending order of T-2 toxin, HT-2 toxin and NEO. Conclusions: This study reveals that CES1 is responsible for the hydrolysis of T-2 toxin, and that fluoride impairs CES1 mediated T-2 toxin detoxification to increase its chondrocyte toxicity. This study provides novel insight to understanding the relationship between fluoride and T-2 toxin in the etiology of KBD.